Testimonio: Oral Histories Woman to Woman - Mueller, RoseAnna Maria (Revista Espaço Acadêmico, 2012)
This text discusses the genre called "testimonio" and how it has become an important component of the study of Latin America in the American schools. The emphasis falls on three books–Me llamo Rigoberta Menchu’ y asi’ me nacio’ la conciencia, Reyita, and Si me permiten hablar...–and the discussion points out the different experiences each of them illustrates.